Pressure ulcers induced by drug administration: A new concept and report of four cases in elderly patients. Issue 4 (14th September 2015) - Mizokami, Fumihiro; Takahashi, Yoshiko; Hasegawa, Keiko; Hattori, Hideyuki; Nishihara, Keiji; Endo, Hidetoshi; Furuta, Katsunori; Isogai, Zenzo
Abstract: Drug‐induced akinesia is a potential cause of pressure ulcers. However, pressure ulcers that are caused by drug‐induced akinesia are not considered an adverse drug reaction (ADR). We propose that drug‐induced pressure ulcers (DIPU) are pressure ulcers that are caused by an external force that is experienced after drug administration, and we considered resolution of these ulcers after drug discontinuation to be a supportive finding. In this report, we reviewed the medical records of pressure ulcer cases from a 300‐bed hospital. Among 148 patients, four patients with pressure ulcers met the criterion for DIPU. In these cases, the suspected DIPU were related to treatment with olanzapine, fluvoxamine, valproic acid, clotiazepam, triazolam and rilmazafone. These drugs were administrated to manage the patients' behavioral and psychological symptoms that accompanied dementia. The DIPU in these patients were categorized as stage IV according to the National Pressure Ulcer Advisory Panel criteria. Discontinuation of the causal drugs led to significant improvements or complete healing of the pressure ulcers, and the patients subsequently recovered their mobility. Therefore, we propose that DIPU are potential ADR that have been overlooked in clinical practice. Thus, recognition of DIPU as an ADR may be important in preventing and appropriately managing pressure ulcers among elderly patients.